The two gentlemen of Verona - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
A story of friendship and how it can overcome all odds, The Two Gentlemen of Verona is another popular romantic comedy by Shakespeare. It is about two inseparable friends, Valentine and Proteus, and how their friendship is affected when they fall in love. Even though their friendship is tested, they deal with their problems and come out better than ever on the other side.
Keywords: Triangles (Interpersonal relations) -- Drama; Exiles -- Drama; Verona (Italy) -- Drama